(untitled) (Diyala Journal of Engineering Sciences, 2017)
تعد المواد المتراكبة المعدنية ذات الأساس من الألمنيوم من أهم المتراكبات المستخدمة في التطبيقات الهندسية المعقدة لما تتميز به من صفات وخصائص جيدة مثل المقاومة العالية بالنسبة للوزن والكثافة المنخفضة ومقاومة البلى. يهدف البحث إلى تصنيع مادة متراكبة هجينة ذات أساس من الألمنيوم ومقواة بدقائق كاربيد التنكستن (WC) وبكسر حجمي ثابت يساوي 3 % علاوة على كسور حجمية متغيرة من دقائق الكرافيت (Gr) تساوي 8, 6, 4, 2, 0 % باستخدام تقانة ميتالورجيا المساحيق ودراسة تأثيرها على الخواص الفيزيائية والميكانيكية والبلى للألمنيوم، إذ تم مزج الخليط لمدة 15 دقيقة باستخدام خلاط ميكانيكي بعدها كبس المزيج على البارد بضغط 500 MPa للحصول على عينات بقطر 12 mm وبارتفاع 6 mm ومن ثم اجري التلبيد بدرجة حرارة 550 oC لمدة ساعتين، تم دراسة بعض الخصائص الميكانيكية للمتراكب وهي الصلادة ومقاومة الانضغاط ومعدل البلى علاوة على الخصائص الفيزيائية المتمثلة بالكثافة الحجمية والظاهرية والمسامية الحقيقية والظاهرية وامتصاصية الماء بالإضافة إلى فحص التركيب المجهري. أظهرت نتائج الدراسة انخفاض كل من الصلادة ومقاومة الانضغاط بنسبة 24 % و 40 % على التوالي بزيادة الكسر الحجمي للكرافيت، أما معدل البلى فقد تم الحصول على أقل معدل بلى أي أعلى مقاومة عند محتوى كرافيت يساوي 2 % ومن ثم يرتفع بعد ذلك بينما أظهرت المادة الأساس المقواة بدقائق كاربيد التنكستن فقط أعلى معدل بلى وأقل مقاومة. كما بينت النتائج وجود علاقة طردية بين الكثافة الحجمية والظاهرية إذ تنخفض بزيادة الكسر الحجمي للكرافيت على عكس كل من المسامية الكلية والظاهرية إذ ترتفع بزيادة محتوى الكرافيت مسببة زيادة امتصاصية الماء للمتراكب الهجين. Metal matrix composites with based of Aluminum are considered among the most important ones that are used in complex engineering application for their good properties; including high resistance to weight ratio, low density, and wear resistance. This work aims to make an Aluminum matrix composite that is reinforced with Tungsten Carbide (WC) particles with constant volumetric ratio of 3% in addition to Graphite particles (Gr) variable volumetric ratios of (0,2,4,6, and 8%) by using powder metallurgical techniques and study the physical, mechanical and wear properties of aluminum. The materials were mixed for 15 minutes using a mechanical mixer, then the mixture was cold compressed to 500 MPa to get samples with 12 mm in diameter, and 6 mm high, then they were sintered at 550 oC for two hours. Some mechanical properties were studied, hardness, compressive strength, wear rate; in addition to the physical properties of volumetric and apparent density, total and apparent porosity, water absorption, and microscopic structure examination. The results showed that hardness and compressive strength were decreased by 24% and 40%, respectively by increasing the volumetric ratio of the graphite. Furthermore, the minimum wear rate, or maximum strength, was obtained at graphite ratio of 2%, then it increases after that, while the based composite reinforced with tungsten carbide only showed maximum wear rate and minimum resistance. Moreover, the results also showed that there is a proportional relationship between the volumetric and apparent densities in which they decrease when the volumetric ratio of the graphite increases. On the contrary, the total and apparent porosity increase by increasing graphite content, causing increase in water absorption for the hybrid composite.